The influence of the portuguese sovereign debt ratings on treasury bond yeilds performance - Tavares, Leinivy (2014)
The rating agencies are often among those accused of taking part in the sovereign debt instability that followed the financial crisis of 2008. This work intends to empirically analyse the influence of changes in the Portuguese sovereign debt rating, as attributed by the three main international rating agencies (Moody’s, S&P e Fitch), in the performance of mid to long-term treasury bond yields (2, 5 and 10 years) over the period between February 2003 and May 2012. Using simple and multiple linear regression models, estimated through the OLS method, and through the application of Chow’s test, the statistical evidence shows that the changes in sovereign debt rating have a negative and significant impact on the performance of treasury bond yields for all maturities studied and this influence is higher for the period after the sovereign debt crisis. The evidence also show that the impact of changes in sovereign debt rating in treasury bond yields increases with the loss of investment grade.